Pengaruh Tata Tertib Sekolah terhadap Kedisiplinan Siswa Kelas VIII di SMP Negeri 1 Kota Solok - Fitri, Adella Hafifah; Syawaluddin, Syawaluddin (Lembaga Yasin AlSys, 2023)
School rules are rules set by the school in order to create order and discipline for students at school. Violations committed by students will create an atmosphere that is not conducive. The background of this research is that the regulations that have been made by the school will determine the discipline of class VIII students of SMPN 1 Solok City. If there are students who are not disciplined, it means ignoring the rules that have been made by the school. The rules are bound by weights that will be a punishment for students who violate school rules. In this study used descriptive qualitative research methods. Data obtained from key informants and supporting informants. The key informant is a BK teacher at SMP Negeri 1 Solok City. And the supporting informants are homeroom teachers of subjects and class VIII students of SMP N 1 Solok City. The technique used in this research is interview and observation technique. In this study, it was revealed that discipline is strongly influenced by discipline because school rules have their respective weights. And if the weight has reached 150, students will be threatened with expulsion from school. The more violations, the more undisciplined the school will be. SMPN 1 Solo city is still able to maintain discipline and does not escape the important role of BK teachers in minimizing violations committed by students.